Double mental foramina - Taruska Ventorini Vasconcelos; Frederico Sampaio Neves; Francisco Haiter-Neto; Deborah Queiroz Freitas
The knowledge of the location, trajectory, and characteristics of the neurovascular bundles in the jaws is fundamental to reduce risk of injuries to this structure during surgical procedures, especially when anatomical variations are present. The presence of anatomical variations associated with the mental foramen has been reported in some cases and is frequently undervalued in clinical procedures. Sensorial disturbances, such as paresthesia in the lower lip or cheeks, may occur as result of pressure on the mental foramen. These anatomical variations can be detected in clinical practice by imaging exams. Computed tomography has been established as a valuable imaging modality capable of providing in-depth information about maxillofacial structures, allowing detailed evaluation of their topography and anatomical variations, such as additional mental foramina. The objective of this article was to describe a case with double mental foramina that only could be observed in computed tomography images. The use of cone beam computed tomography has increased in dentistry, thus anatomical variations that may have an influence on the diagnosis and treatment planning must be recognized. Have a good knowledge of additional mental foramina may contribute to adequate anesthetic techniques and to avoid misdiagnosis of bone lesions and eventual damages to the nerves and vessel during surgical procedures in that region.